Catalyzing progress in the blue economy through joint marine microbiome research across the Atlantic - Ortmann, Alice C.; Goodwin, Kelly D.; Bolhuis, Henk; Groben, René; Makhalanyane, Thulani; Bowman, Jeff; Robinson, Shawn; Thompson, Fabiano (Frontiers in Marine Science, 2023)
International agreements recognize the importance of cooperative scientific research to conserve and promote sustainable development of a shared Atlantic Ocean. In 2022, the All-Atlantic Ocean Research and Innovation Alliance Declaration was signed. The All-Atlantic Declaration continues and extends relationships forged by the Galway Statement on Atlantic Ocean Cooperation and the Belém Statement on Atlantic Ocean Research and Innovation Cooperation. These efforts are consistent with programs, actions, and aims of the United Nations Decade of Ocean Science for Sustainable Development. In preparation for implementation of the All-Atlantic Declaration, members of the Marine Microbiome Working Group and the Marine Biotechnology Initiative for the Atlantic under the Galway and Belém Statements respectively, joined forces to call for cooperation across the Atlantic to increase marine microbiome and biotechnology research to promote ocean health and a sustainable bioeconomy. This article reviews the goals of the marine microbiome and biotechnology initiatives under the Galway and Belém Statements and outlines an approach to implement those goals under the All-Atlantic Declaration through a Blue Biotech and Marine Microbiome (BBAMM) collaboration.